الإنتانات المهبلية ومعرفة الأم لجنس الجنين وأثرهما على وزن الولادة - حمود, زبيدة خضر (Latakia University Journal -Medical Sciences Series, 2019)
دراسة تأثير معرفة الأم لجنس الجنين بالأمواج ما فوق الصوت خلال فترة الحمل. تبين أن وزن الوليد الذكر أكبر منه عند المولود الأنثى بوسطي حساب 3313 غرام للذكر مقابل 3185 للمولود الأنثى. (3) بالدراسة لمجموعة تعدادها 1039 حاملاً للفلورا المهبلية والإنتان المهبلي. تبين أن الحوامل المصابات بالإنتان المهبلي أكثر عرضة لولادة مبكرة ونقص وزن الوليد. (3) كشفت الإصابة في 16% منهن حيث ينقص وزن الوليد وولادة مبكرة.(3) Study of the effects of the mother's realization of the fetus' sex using ultra sound during pregnancy. It turns out that the weight of the male newborn is more than female newborn in a rate of 3313 g for male newborn and 3185 g for female newborn.(3) Testing a group of 1039 to the carries of the vaginal flora and vaginal infections shows that pregnant women with vaginal sepsis are more likely to give early birth and under weight of the newborn.(3) It reveals that 16% of them are having underweight newborn babies and per mature birth.(3)